2016
DOI: 10.1177/1535370216675773
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of interleukin-2 to effective wound healing

Abstract: Ineffective skin wound healing is a significant source of morbidity and mortality. Roughly 6.5 million Americans experience chronically open wounds and the cost of treating these wounds numbers in the billions of dollars annually. In contrast, robust wound healing can lead to the development of either hypertrophic scarring or keloidosis, both of which can cause discomfort and can be cosmetically undesirable. Appropriate wound healing requires the interplay of a variety of factors, including the skin, the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 110 publications
(196 reference statements)
0
43
0
2
Order By: Relevance
“…Another avenue of further experimentation would be to explore quercetin's effects on other cell types that participate in wound healing, including skin cells such as melanocytes or keratinocytes, immune participants in wound healing such as neutrophils, macrophages, lymphocytes or histiocytes, or cells that mediate neovascularization such as smooth muscle cells or vascular endothelial cells. 1 A more complete examination of the impact of quercetin on all the cells present at the wound site would not only improve our understanding of how quercetin could prevent the formation of ECM fibers in wounds and thereby decrease scarring but might also help identify other therapeutic targets by which wound healing could be improved. Thus, more work is needed to better understand the mechanism by which quercetin improves wound healing to fully utilize its therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another avenue of further experimentation would be to explore quercetin's effects on other cell types that participate in wound healing, including skin cells such as melanocytes or keratinocytes, immune participants in wound healing such as neutrophils, macrophages, lymphocytes or histiocytes, or cells that mediate neovascularization such as smooth muscle cells or vascular endothelial cells. 1 A more complete examination of the impact of quercetin on all the cells present at the wound site would not only improve our understanding of how quercetin could prevent the formation of ECM fibers in wounds and thereby decrease scarring but might also help identify other therapeutic targets by which wound healing could be improved. Thus, more work is needed to better understand the mechanism by which quercetin improves wound healing to fully utilize its therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…1 These larger, slow to heal wounds can be problematic and can lead to significant sequelae or even death. It is estimated that more than 6.5 million Americans were afflicted with chronic wounds in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 1 is primarily sourced from macrophages in the event of injury, infection, and antigenic challenge although the epidermal, epithelial, lymphoid, and vascular Wound Healing -Current Perspectives tissues also serve as reservoirs for the polypeptide [11]. The actions of IL-1 span from systemic changes in the neurological, hematologic, endocrinologic, and metabolic systems to some local effects that are particularly relevant in wound healing [12]. By influencing both destructive and repair processes, it contributes the mesenchymal tissue remodeling, and it does so by influencing quite a number of cells.…”
Section: Interleukin 1 (Il-1)mentioning
confidence: 99%
“…Also Gly, with the production of interleukin-1 (IL-1), IL-2, and IL-12 increase antibody production [33]. Interleukin-2, as a cytokine with effect on the T-cell, has a key role in wound healing [5]. It was shown that G. glabra, is effective for the treatment of skin diseases such as dermatitis, eczema and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…So, trying to quickly close the cutaneous wound with functional and aesthetic results would be ideal goal of treatment [4]. On the other hand, impaired wound healing is the main source of mortality and morbidity, that is associated with high costs [5]. Natural products are safe, less side effect, cultured acceptability and with having excellent physiological properties are the source of new treatments for cutaneous wound healing [6].…”
Section: Introductionmentioning
confidence: 99%